2020
DOI: 10.1186/s12985-020-01315-z
|View full text |Cite|
|
Sign up to set email alerts
|

Anti-HSV-1 activity of Aspergillipeptide D, a cyclic pentapeptide isolated from fungus Aspergillus sp. SCSIO 41501

Abstract: Background: Herpes simplex virus 1, an enveloped DNA virus belonging to the Herpesviridae family, spreads to neurons and causes pathological changes in the central nervous system. The purpose of this study was to investigate the potency and mechanism of antiviral activity of Aspergillipeptide D, a cyclic pentapeptide isolated from a culture broth of marine gorgonian-derived fungus Aspergillus sp. SCSIO 41501, At present, there are many studies on the anti-tumor, anti-clotting, anti-oxidant and immunoinflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…In conclusion, twelve compounds, including three new compounds (1-3), and nine known compounds (4)(5)(6)(7)(8)(9)(10)(11)(12) were isolated by fractionation of the EtOAc extract prepared from a rice fermentation culture of Aspergillus sp. WHUF03110.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, twelve compounds, including three new compounds (1-3), and nine known compounds (4)(5)(6)(7)(8)(9)(10)(11)(12) were isolated by fractionation of the EtOAc extract prepared from a rice fermentation culture of Aspergillus sp. WHUF03110.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 1, the promising compounds for 3CLpro-CoV2 or PLpro-CoV2 inhibitors are dominated from Aspergillus groups. Antiviral activity of Aspergillus groups against some viruses are widely reported [102][103][104][105], nevertheless no report for experimental evidence on the antiviral properties of this group against living SARS-CoV-2 exists. Interestingly, Koehler et al [106] reported that COVID-19 patients are more susceptible towards invasive pulmonary aspergillosis (IPA).…”
Section: Microorganisms As Sources Of Inhibitors Targeting Sars-cov2 Proteasesmentioning
confidence: 99%
“…Further, a compound name apigenin is found to create obstacles in the cell to cell virus spread [153]. Research on Aspergillipeptide D revealed that though it doesn't interrupt in HSV-1 viral infection stages but dramatically it reduces both gene and protein levels including viral late protein gB and found to suppress its location on endoplasmic reticulum and Golgi apparatus [154]. Besides, Omeprazole was found to increase the anti-cancer effect of nucleoside analog 5-fluorouracil without affecting ribavirin in nontoxic concentration (up to 80 mg/mL).…”
Section: Current Status and Future Prospects Of Hsv-1 Researchmentioning
confidence: 99%